Fuzzy Logic Control in Energy Systems with design applications in MATLAB®/Simulink - Altas, Ismail H (The Institution of Engineering and Technology, 2017)
Modern electrical power systems are facing complex challenges, arising from distributed generation and intermittent renewable energy. Fuzzy logic is one approach to meeting this challenge and providing reliability and power quality. The book is about fuzzy logic control and its applications in managing, controlling and operating electrical energy systems. It provides a comprehensive overview of fuzzy logic concepts and techniques required for designing fuzzy logic controllers, and then discusses several applications to control and management in energy systems. The book incorporates a novel fuzzy logic controller design approach in both Matlab® and in Matlab Simulink® so that the user can study every step of the fuzzy logic processor, with the ability to modify the code. Fuzzy Logic Control in Energy Systems is an important read for researchers and practicing engineers in energy engineering and control, as well as advanced students involved with power system research and operation.